Evaluation of pediatric patients presenting with acute-onset unilateral transient acquired blepharoptosis - KIRIK, FURKAN; KIRIK S.; KIRIK F.; YURTTUTAN N.; Gungor O.; Acipayam C. (My University, 2022)
Purpose: To evaluate the clinical features of pediatric patients with acute-onset, unilateral transient acquired blepharoptosis. Methods: In this retrospective study, the clinical records of patients between April 2015 and June 2020 were reviewed for evaluation of demographic features, accompanying neurological and ophthalmologic manifestations, symptom duration, etiological cause, and imaging findings. Patients with congenital and acquired blepharoptosis with chronic etiologies were excluded. Results: Sixteen pediatric patients (10 boys and 6 girls) with acquired acute-onset unilateral transient blepharoptosis were included in this study. The patients' mean age was 6.93 ± 3.16 years. The most commonly identified etiological cause was trauma in 7 patients (43.75%) and infection (para-infection) in 5 patients (31.25%). In addition, Miller Fisher syndrome, Horner syndrome secondary to neuroblastoma, acquired Brown's syndrome, and pseudotumor cerebri were identified as etiological causes in one patient each. Additional ocular findings accompanied blepharoptosis in 7 patients (58.33%). Blepharoptosis spontaneously resolved, without treatment, in all the patients, except those with Miller Fisher syndrome, neuroblastoma, and pseudotumor cerebri. None of the patients required surgical treatment and had ocular morbidities such as amblyopia. Conclusion: This study demonstrated that acute-onset unilateral transient blepharoptosis, which is rare in childhood, may regress without the need for surgical treatment in the pediatric population. However, serious pathologies that require treatment may present with blepharoptosis.
Keywords: Blepharoptosis; Craniocerebral trauma; Infectious disease; Miller Fisher syndrome; Horner syndrome; Child